Seroprevalence of Contagious Caprine Pleuropneumonia (CCPP) in Bharatpur, Chitwan, Nepal - Regmi, LB; Manandhar, S; Gongal, L; Poudel, S; Acharya, RC; Subedi, D (Nepalese Veterinary Journal, 2023)
A study was conducted to determine the seroprevalence of Contagious Caprine Pleuropneumonia (CCPP) in 106 goats of Bharatpur Municipality of Chitwan, Nepal from July to October 2021. A questionnaire was used to determine the potential risk factors. Collected samples were subjected to a competitive enzyme-linked immunosorbent assay (cELISA) for the detection of antibodies. The seroprevalence of Contagious Caprine Pleuropneumonia in goats was 4.71% (5/106). Although seroprevalence was high among females and goats below or equal to 5 years, there was no statistically significant. This study was carried out in the Chitwan district for the first time, applying the (Mccp) Antibody test technique, considering the need for control of this economically important disease for poor livestock farmers in Chitwan and it can play important role in the epidemiological study of CCPP in Nepal.